2017
DOI: 10.1111/1750-3841.13839
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Maillard Reaction on the Immunoreactivity of Amandin in Food Matrices

Abstract: Foods containing almond are often subjected to processing prior to consumption. Amandin, the major allergen in almond, may experience Maillard reaction. Understanding the change in amandin immunoreactivity as a result of Maillard reaction is important for amandin detection and production of hypoallergenic food products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 34 publications
1
7
0
1
Order By: Relevance
“…This process may require chronic antigen exposure, as it took several immunizations with a mixture of different protein-MAGEs to generate anti-MAGE antibodies in mice (see "Methods"). The other authors have observed similar types of cross reactivity [36][37][38] . The in vivo biosynthetic pathway of native MAGE formation and whether MAGEs can be delivered with diet remain to be elucidated.…”
Section: Discussionsupporting
confidence: 63%
“…This process may require chronic antigen exposure, as it took several immunizations with a mixture of different protein-MAGEs to generate anti-MAGE antibodies in mice (see "Methods"). The other authors have observed similar types of cross reactivity [36][37][38] . The in vivo biosynthetic pathway of native MAGE formation and whether MAGEs can be delivered with diet remain to be elucidated.…”
Section: Discussionsupporting
confidence: 63%
“…One study reported that MR reduced the IgG reactivity of almond 11S legumin [ 108 ]. Although the paper did not report its IgE reactivity, the IgG antibody used (4C10) targets a conformational epitope that overlaps with IgE-binding epitopes [ 109 ], so it may also affect its IgE binding capacity.…”
Section: Maillard Reaction and Allergenicity Of Foodsmentioning
confidence: 99%
“…Analyses of almond protein extract has been extensively carried out and it was found that prunin is a major component of the nut, accounting for up to 65% of the protein in the soluble extract (da Costa, 2013). Analysis revealed that the overall structure of amandin is typical of the 11S globulin class of seed storage proteins, as it is composed of two prunin trimers that associate to form the native hexameric structure (Chhabra, 2013).…”
Section: Amandin 11s Globulin From Almondmentioning
confidence: 99%
“…Globulin protein was composed of acidic polypeptide (30-33 kDa) and a single basic polypeptide (20-24 kDa), isolated amandin protein was composed of acidic polypeptide (40-42 kDa) and a single basic polypeptide (15-20 kDa) and isolated cucurbitin protein was composed of acidic polypeptide (35-42 kDa) and and a basic polypeptide (20-25 kDa) (McNulty, 2006;Chhabra, 2013;. Amandin is an 11S globulin legumin-like protein that is hexameric in form and composed of individual polypeptides (Bojórquez-Velázquez et al, 2016).…”
Section: Globulin Protein Of Sesame Seeds Amandin Protein Of Almond mentioning
confidence: 99%